Association of Absolute Lymphocyte Count and Circulating CD4+ and CD8+ T-Cells with Positive Clinical Outcome in Survivors of Cancer: An Observational Study - Suresh Rao; Venkatesh Ponemone; Krishna Prasad; Sanath K. Hegde; Prajna D'silva; Manjeshwar Shrinath Baliga (Indian Journal of Medical Specialities)
Background: The objective of this observational study is to determine the changes in the circulating immune cells as a predictor of outcomes in patients who have survived cancer. Materials and Methods: A peripheral blood immune-profile evaluation was performed in all the survivors of cancer (n = 66) during their visit to the hospital for regular follow-up and thereafter followed up for two consecutive years for any morbidity or mortality. The changes in hematological and biochemical parameters were evaluated in all the patients. The frequency of circulating lymphocyte cell population i.e., CD3+, CD4+, and CD8+ lymphocytes were analyzed using flow cytometry in the peripheral blood of the patients. The variability in the circulating lymphocytes was correlated with tumor relapse and overall survival (OS). Results: In the study, 47 of the 66 patients with cancer survived at the end of 2 years observation time period, while 19 patients died due to infection related complications and not due to tumor relapse. A significant reduction in the neutrophil (P < 0.0001) and lymphocyte (P < 0.0001) counts were observed in patients who succumbed to the illness within 2 years when compared to the cohorts that were surviving. A statistically significant reduction in the absolute lymphocyte counts (P < 0.004), absolute CD3 (P < 0.0001), CD4 (P < 0.002), and CD8 (P < 0.04) were observed in the deceased group compared to the surviving group. CD4/CD8 ratios between both live and deceased groups did not show any significant difference. Conclusion: This preliminary observational study indicates a correlation of circulatory lymphocytes to OS in survivors of cancer and that it could be a predictive marker.